Ceda Land Miniaturisation and Class Formation in Africa: A Re-Assessment (Bugisu Region, Eastern Uganda) - Charles Edaku (International Journal on Economics, Finance and Sustainable Development, 2022)
This paper analyses the role of land miniaturisation and commuting in class formation in Africa with reference to East and Central Uganda. It presents the argument that land miniaturisation in East and Central Uganda coalesced with ineffective mechanisms of resource allocation have led to rapidly decreasing availability of natural resources for rural households resulting into new changes in the agrarian economy and thus commuting. The changes in the economy have had far reaching effects on traditional livelihoods of the rural population in Africa and Uganda in particular leading to emergence of new production relations. The discussion presented in this paper fits well into John Murton’s (1997) analysis of the agrarian changes in Machakos, Kenya in which farmers have become more dependent on non-agricultural sources of livelihoods. It embraces Karl Marx theory on production relations between the proletariats and bourgeoisie ingrained in access to and ownership of capital. It fits into Max Weber’s analysis of class formation in his book “The Protestant Ethic and Spirit of Capitalism”. I take the case of commuting phenomenon in the East and Central Uganda to piece together my arguments. Conclusions are drawn from both primary and secondary sources.